2018
DOI: 10.1111/jfpp.13757
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and antimicrobial efficacy of watermelon rind extract (WMRE) in aerobically packaged pork patties stored under refrigeration temperature (4±1°C)

Abstract: The present study was undertaken to evaluate antioxidant and antimicrobial efficacy of ethanolic extract of watermelon rind (WMRE) incorporated at 0.10% level in pork patties. The selected patties along with positive control (with 0.02% butylated hydroxyl anisole) and control samples were packaged in aerobic packaging and evaluated for various oxidative and microbiological stability parameters for 28 days under refrigeration (4 ± 1°C). The indicators of lipid peroxidation viz. thiobarbituric acid reactive subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
28
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 30 publications
2
28
0
1
Order By: Relevance
“…Watermelon peel extracts inhibited significantly both brown-rot fungi in this study, but did not inhibit the whiterot fungus T. versicolor. Watermelon peel extracts are effective as food preservatives [17] as well as inhibitors of health issue related bacteria and fungi [18]. The results of this work together with previous findings prove that watermelon peel extracts at tested concentration are able to inhibit several fungi, but some others, such as T. versicolor, are not sensitive to them.…”
Section: Resultssupporting
confidence: 71%
“…Watermelon peel extracts inhibited significantly both brown-rot fungi in this study, but did not inhibit the whiterot fungus T. versicolor. Watermelon peel extracts are effective as food preservatives [17] as well as inhibitors of health issue related bacteria and fungi [18]. The results of this work together with previous findings prove that watermelon peel extracts at tested concentration are able to inhibit several fungi, but some others, such as T. versicolor, are not sensitive to them.…”
Section: Resultssupporting
confidence: 71%
“…The higher value for T2 and T3 could be due to bromelain and ficin present in pineapple and fig powder, respectively in addition to calcium and minerals. A comparable collagen content in buffalo meat ( Naveena et al, 2011 ) and in emu meat chunks ( Verma et al, 2018b ) in presence of different tenderizers had been also reported. Collagen solubility of T2 samples was recorded highest and significantly (p<0.05) higher than T3, which exhibited significantly (p<0.05) higher value than T1.…”
Section: Resultssupporting
confidence: 57%
“…This increased pH on cooking compared to raw product could be due to denaturation of meat proteins at higher temperature and formation of imidazolium compounds from amino acids having imidazole side chain as well as with reaction between ammonia and aldehydes. Kumar et al (2018a ; Kumar et al, 2018b ) also reported similar increase in pH upon cooking in pork patties incorporated with sapota powder and watermelon rind extracts. The lower pH of T2 and T3 samples could be due to low pH of pineapple peel powder (4.12) and fig powder (5.63).…”
Section: Resultsmentioning
confidence: 65%
See 2 more Smart Citations